Influence of Corporate Social Responsibility on Brand Image of Commercial Banks - K.C., Sudarshan (Mangal Research Journal, 2022)
Corporate Social Responsibility (CSR) has been a strategy of banks to respond to the society in which they operate activities so that they can enhance their brand image. It encourages banks to make a positive contribution to the society. A good image of a bank is an asset because it has positive impact on its customers’ perception and preference about the bank. There are few empirical investigations that relate CSR and brand image in Nepalese banks. For this reason, the purpose of the study is to explore the relationship between economic, legal, ethical and philanthropic responsibility on brand image of Nepalese commercial banks. Quantitative research approach was followed for the purpose. Data was collected from 210 valid questionnaires received from respondents met around Kirtipur. The responses were analyzed using SPSS 25 version. The findings revealed that there is a significant and positive influence of economic, legal, ethical and philanthropic responsibility on brand image of Nepalese commercial banks. The result of this study can be used by CEOs and marketing executives to develop strategies that make use of CSR as a strategy for building brand image.